Finite element analysis of a 20 structural frame of a wing box test stano / Siti Syahioah Moho Rum - Moho Rum, Siti Syahioah (2009)
Test stands are designed and built to test the performance of the structures against the targets set in the design specification. This study reports on the finite element analysis of a 20 structural frame of a wing box test stand. In this study, two types of structural analyses of the test stand are conducted which are static analysis and buckling analysis. The static analysis is conducted to determine displacements, stresses; and deflection . under static loading, whereas the buckling analysis is done to determine buckling loads and the buckling mode shape. The finite element analysis is accomplished using ANSYS/ED and ANSYS 11.0. Results from the finite element analysis were then compared with the results obtained by formulation. The material used for this project is a hot rolled tube mild steel (A36). It is expected that this study can contribute to practical research for mechanical engineering student